Reappraisal of immunohistochemical profiling of special histological types of breast carcinomas: a study of 121 cases of eight different subtypes - Alvarenga, Cesar Augusto; Paravidino, Paula Itagyba; Alvarenga, Marcelo; Gomes, Madalena; Dufloth, Rozany [UNESP]; Zeferino, Luiz Carlos; Vassallo, Jose; Schmitt, Fernando C. (B M J Publishing Group, 2012)
Histological special types (HST) account for about 25% of breast cancers, and correspond to at least 17 pathological entities. However, their molecular characteristics remain to be determined. The purpose of the present study is to apply the recently used immunohistochemical profiling of HST breast carcinomas (BC), as a surrogate for the molecular subtyping, what could be relevant for therapeutic purposes. One hundred and twenty-one cases were included. Immunohistochemical study was performed on paraffin sections, including markers for oestrogen, progesterone and androgen receptors, keratin 5, HER2/neu, epithelial growth factor receptor, p63 protein, P-cadherin, and Ki-67. Tubular (16 cases), mucinous (27) and papillary (9) types were all categorised as luminal-like A and B. The medullary (21) and metaplastic (10) types corresponded largely to the basal-like tumours (85.7% and 90%, respectively). Cases of the micropapillary type (8) were luminal A (3/8), luminal B (4/8) and HER2 overexpressing (1/8), whereas the apocrine carcinomas (24) presented a heterogeneous profile. The proliferation rate (Ki-67) varied among the types, being the medullary carcinoma subtype with higher proliferation. Comparing the current data with those based on molecular studies, there was good agreement in the classification of the tubular, mucinous and papillary types. Only a partial concordance was achieved for the other types, which may be due to sampling, and to the relatively low frequency of such cases. The present work supports the clinical usage of immunohistochemistry as a surrogate to molecular classification of special types of BC.